Spatial distribution of the species of the genus buenoa (hemiptera: notonectidae) in tumaco (nariño, colombia) (2014)
ABSTRACT The work was carried in the Mar Agrícola farm of the municipality Tumaco, with the objective of studying the distribution of the species of the genus Buenoa in homogeneous environmental conditions regarding temperature, humidity, altitude and aquatic habitats of the freshwater and the others with different grade of conductivity and dedicated to the marine shrimp farming Litopenaeus vannamei (Boone, 1931). The studied lakes were four of freshwater and four with different conductivity, in the months of June to November 2010. The results showed heterogeneous distribution of the species of the genus Buenoa with major diversity in freshwater (5 species) and lower abundance; while in saltwater had lower diversity (4 species) and major abundance. Only Buenoa dactylis Padilla-Gil 2010 was found in both aquatic environments. It is discussed possible ecological implications than can influence this distribution pattern are discussed. RESUMEN El trabajo se realizó en la finca Mar Agrícola del municipio de Tumaco, con el objetivo de estudiar la distribución de las especies del género Buenoa en condiciones ambientales homogéneas respecto a la temperatura, humedad y altitud, en hábitats acuáticos de agua dulce y otros, con diferentes grados de conductividad y dedicados al criadero del camarón marino Litopenaeus vannamei (Boone, 1931). Los lagos estudiados fueron cuatro de agua dulce y cuatro con diferente conductividad, en los meses de junio a noviembre del 2010. Los resultados indican la distribución heterogénea de las especies del género Buenoa con mayor diversidad en ambientes dulceacuícolas (5 especies) y menor abundancia; mientras en ambientes salobres hay menor diversidad (4 especies) y mayor abundancia. Solo la especie Buenoa dactylis Padilla-Gil 2010 se encuentra en ambos ambientes acuícolas. Se discute posibles implicaciones ecológicas que puedan influir en este patrón de distribución.